Answer:
The solution is -24, the first choice.
Step-by-step explanation:
The given equation is
[tex]\frac{2}{3}(\frac{1}{2}x+12 )=\frac{1}{2}(\frac{1}{3}x+14 ) -3[/tex]
First, we use distributive property
[tex]\frac{2}{6}x+\frac{24}{3}=\frac{1}{6}x+\frac{14}{2}-3[/tex]
Then, we simplify fractions
[tex]\frac{1}{3}x+8=\frac{1}{6}x+7-3[/tex]
Now, we move all variables to the left and all constants to the right, and solve for [tex]x[/tex]
[tex]\frac{1}{3}x-\frac{1}{6}x=4-8\\\frac{6-3}{18}x=-4\\ \frac{3}{18}x=-4\\\frac{1}{6}x=-4\\ x=-24[/tex]
Therefore, the solution is -24, the first choice.